Menetrier's disease exacerbating ulcerative colitis and relieved by gastrectomy. Issue 1 (20th December 2021) - Kayes, Tahrima; Bonnichsen, Mark; Willmann, Laura; Lorenzo, Aldenb; Das, Amitabha; El-Haddad, Carlos; Househ, Zaid; Ng, Weng; Ng, Watson; Williams, Astrid-Jane; Prince, David; Connor, Susan J
Abstract : Ménétrier's disease (MD) is a rare gastropathy characterised by giant rugal folds which can present with nausea, vomiting, abdominal pain and protein losing gastropathy. We report a 21-year-old woman with comorbid MD and ulcerative colitis (UC). Management was complicated by limited treatment options for MD, significant symptom burden, worsening nutrition and difficulty determining which disease was the predominant cause of symptoms. Since age 18 the patient experienced recurrent UC flares characterised by diarrhoea, persistent vomiting and corticosteroid dependence. Endoscopic assessment demonstrated concurrent MD and active UC. Octreotide and cetuximab were trialled given persistent hypoalbuminaemia and suspicion for MD associated protein-losing gastropathy. UC management comprised dose-optimised infliximab and methotrexate. Repeat endoscopic assessment demonstrated improvement in UC without corresponding improvement in symptoms or hypoalbuminaemia. Nasojejunal feeding and parenteral nutrition failed to significantly improve nutritional status and accordingly the patient proceeded to radical total gastrectomy. Postoperatively, MD-associated symptoms and hypoalbuminemia resolved completely.